On Metrics-Driven Homepages: Assessing the relationship between popularity and prominence. (11th June 2018) - Zamith, Rodrigo
Abstract : As audience analytics systems have proliferated in newsrooms, scholars have expressed fears of, and in some cases assumed a shift toward, a metrics-driven workflow where certain gatekeeping decisions are made based on real-time measures of news consumption. This study evaluated the relationship between a news item's popularity and its subsequent prominence through a two-month analysis of the homepages of 14 news organizations. The results indicated a large divergence between popular and prominent items and limited effects of an item's popularity on its subsequent prominence and risk of removal from prominent areas of the homepage. The findings give pause to fears of an injudicious turn toward an "agenda of the audience, " at least in the context of content placement, and point to directions for future research on the content-related impacts of audience metrics and analytics.